Coordinated matrix deformation induced ductility in multilayer graphene/aluminum composites. (15th January 2023) - Ju, Boyu; Yu, Zhenhe; Gou, Huasong; Yang, Wenshu; Chen, Guoqin; Wu, Gaohui
Abstract: A new strategy to improve strength and ductility by coordinated deformation mechanism of multilayer graphene (MLG) in graphene/aluminum composite was proposed, and the coordinated deformation induced ductility in MLG/Al composite by in-situ tensile tests in this work. Fabricated by a three-step powder metallurgy routes, including flaky ball-milling, horizontal sintering by spark plasma sintering and vertical hot-extrusion, the microstructure of densely distributed MLG with aligned orientation in aluminum matrix was achieved in the MLG/Al composite to take full advantage of MLG in enhancing ductility. Besides 22% and 15% increment in yield and tensile strength, the composite exhibited exciting 11% increment in ductility, which originated from good uniform elongation (6.8%) and especially excellent post-necking elongation (9.5%) which was increased 69% than that of the Al matrix. The evolution behavior of graphene during deformation was analyzed by in-situ TEM. In-situ analysis revealed that the premature fracture before necking was suppressed by rotation and straightening of MLG, while the post-necking elongation was improved substantially by the crack bridging, interlayer sliding and asynchronous delamination fracture of the MLG. Distinguished to the traditional characteristics of dimples, fractured MLGs were mainly distributed along tear ridge of Al dimple with a novel cicada wings-like morphology attributed to the coordinated deformation behavior. Graphical abstract: Image 1